Book Review: Young Muslim Change-Makers; Grassroots Charities Rethinking Modern Societies - Maliha, Hasna (SMART Insight, 2024)
This article summarizes William Barylo's work examining the dynamics of social movements and philanthropy among young Muslims in Europe through field studies of eleven organizations in France, Poland, and the UK. The book highlights the emergence of small-scale Muslim charities initiated by the younger generation within the contexts of secularism, Islamophobia, and contemporary social crises. Using a phenomenological approach, Barylo explores how religiosity, identity, and social participation shape the activism of young Muslims, which is not only religious but also political and humanistic. Through social charity, they reveal a face of Islam that is humanistic, active, and progressive—not as objects of policy, but as subjects of social change. This movement proves that Islam can be a source of social innovation and participatory democracy in Europe.